Synergistic Effects of Magnesium and Zinc Ions on Neural Stem Cell Proliferation and Differentiation - Kim, Hyewon; Kim, Taeyeon; Rahaman, Khandoker Asiqur; Kwon, Jieun; Lee, Ji-Young; Cho, Seohyeon; Chung, Seok; Han, Hyung-Seop; Kim, Yu-Chan (J O M Institute, 2025)
Regeneration of the central and peripheral nervous system is challenging because of the inherent low regenerative capacity. Transplantation of neural stem cells (NSCs) is a promising strategy to increase regenerative capacity, but limited viability, slow proliferation, and differentiation create significant hurdles. Combining neurostimulator bio-functional ions such as magnesium (Mg2+) and zinc (Zn2+) to mitigate this limitation could be a breakthrough for future nerve regeneration treatments. This is the first study to investigate the effects of combined Mg2+ and Zn2+ ion therapy on the proliferation and differentiation of NSCs. The results showed an optimal concentration of Mg2+ and Zn2+ ions individually improved NSC proliferation, with a synergistic effect observed when ions were combined. The synergistic effect also significantly enhanced neurite outgrowth, promoted advanced neuronal network formation, and increased Nestin, beta III-tubulin, and MAP2 gene expression. These findings highlight the potential of combination therapy of Mg2+ and Zn2+ ions, which can be used as complementary modulators with NSCs-based treatments, providing promising ion-based therapeutic strategies in neural repair and regenerative medicine.